Information, identification, or neither? Experimental evidence on role models in Viet Nam - Gaia Narciso; Carol Newman; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
How can development programmes reach out to remote communities? This paper presents experimental evidence on the impact of a role models intervention that aims to inspire ethnic minority households to start businesses and diversify income sources. The experiment took place in three provinces of the Northern highlands of Viet Nam. The research design enables us to disentangle the extent to which role models shift behaviour by providing information or inspiration. We find that despite successful implementation of the intervention, which was powered to detect reasonably small effects, and a high level of compliance, the role model intervention did not impact on income, livelihoods, or other welfare outcomes. This points to the difficulties involved in using role models to induce behavioural change in contexts where populations are severely marginalized and face a variety of binding constraints.
Keywords: D1; D3; I3; O12; 330; role models; RCT; ethnic minorities; Viet Nam